DIAGNÓSTICO DE METAIS EM FRAÇÕES ABIÓTICAS E BIÓTICAS DO ENTORNO DO REFÚGIO BIOLÓGICO DE SANTA HELENA - PR - Roos, Andreine Aline (2021)
Metals are found naturally in soils and sediments, from weathering and leaching. However, its profile in the environment has been altered due to anthropogenic activities, which may cause damage to living beings due to its persistence, toxicity, bioaccumulation and biomagnification. The Santa Helena Biological Refuge (RBSH) is a conservation unit (UC) bathed by the Itaipu reservoir that receives influence from such activities. Thus, the objective of this study was to make a diagnosis of the abiotic (soil and sediment) and biotic (fish) fractions in relation to the metal contents around the RBSH. Physical and chemical parameters were determined in 16 soils, covering three classes, and 9 sediments in four climatic seasons of 2019. For the quantification of metals in fish, the liver, gills and muscle of the species Hoplias malabaricus (HM) and Schizodon borelli (SB) were used. The extraction of metals in soils was based on the USEPA 3050B method, in sediments by the sequential Tessier extraction and in fish by alkaline solubilization, and quantification was performed by flame atomic absorption spectrometry (F AAS). Similar soils and sediments have similar values for physical and chemical parameters, except for the available P, and were characterized as clayey and slightly acidic, which is due to their basaltic origin. The principal component analysis (PCA) was able to separate the soils into four groups, two of which are characterized mainly by the greater cation exchange capacity (CTC) and potential acidity and the other two by the organic matter contents and by clay and by base saturation percentage (V%), therefore with a greater tendency to retain metals. In relation to sediments, there was no separation of standards by recommendation. The levels of non metals in RBSH were similar to the quality reference values (QRV) of local and of soils of basaltic origin from other Brazilian regions, except for Pb, indicating a possible contamination by atmospheric or deposition originating before the creation of the UC. The soil classes of Oxisol (Ox) and Ultisol (Ult) had the highest levels of metals due to the greater acidity, clay and organic matter contents. In soils the metals Pb and Cr were positively correlated by the Pearson matrix, as well as Cu, Zn and Fe. The sum of the metals of the fractions from the sequential extraction of the sediments around the RBSH indicated that the contents were lower than in the soils and that no metal exceeded the PEL value (level of probable effects), that is, they only present occasional risks to the biota. Metals are preferentially bound to Fe and Mn oxides and hydroxides in sediments, due to their basaltic origin. The statistical indices showed that the metals in the sediments are of natural origin, with the exception of Cr and Pb which is a possible contamination, but do not represent ecological risks. In fish, the metal contents were higher for HM than for SB, due to its trophic level, which is indicative of biomagnification. The muscle that is the edible part of the fish has metal values that are safe for human consumption. However, the liver was the tissue with the highest metal content, exceeding the limits defined by legislation, especially for Pb and Cd, indicating a possible influence of anthropogenic activities in the study site. Thus, despite the increase in Pb, Cr and Cd, the risks of these metals associated with the biota surrounding the RBSH are low, making it possible to use the study site as an environmental preservation area. However, it is necessary to carry out monitoring for a longer period to verify whether the pattern in the distribution of metals between seasons will repeat and proportions for the conservation of this important aquatic ecosystem.